Influence of Household Decision Making on Income Inequality - Mirzo, Shabnami (2019)
The thesis revolves around how individuals play a role in the level of income inequality through the decisions they make, whether that be; (i) level of consumption, (ii) savings and investment, (iii) time allocation and hours worked, (iv) the rate of female labour participation and (v) religiosity. Regression analysis performed for aforementioned decisions on measures of inequality, through Ordinary Least Squares (OLS) regression model. Countries chosen for analysis were Czech Republic, South Africa, Tajikistan and United States. The Czech Republic and South Africa were chosen based on being counterparts in the area of the measures of inequality. In contrary, Tajikistan and United States were chosen based on being counterparts in the area of Gross Domestic Product (GDP). Data sources used include the Global Consumption Income Project (GCIP), the International Labour Organization Database (ILOSTAT), European Social Survey (ESS), World Values Survey (WVS), OECD Library, etc.. In addition, an online survey was conducted to identify preferences based on income group when choosing who to marry. Results from the regression showed that most of the decision variables were significant in all countries. There were different trends amongst the countries for each variable, some having negative relationships, positive. The trends were backed up by the characteristics and circumstances of the country. Female labour participation had most significance, but rather a positive relationship- where if more females worked, income inequality would increase.The data was also tested for reverse causality, to which it was present in most of the decisions, paving way for perception that individual can be constrained by their income and unfair distributions.